(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
This article deals with the variations around the concept of social contract, from its understanding as a historical fact, responsible for the transition from the state of nature to a condition of life in society, to its understanding as a regulatory ideia, responsible for the organization of the institutions as we know. This will be done by describing and analyzing theoretical discussions that collaborated to the development of a legal theory regarding the social contract, taking into account historical and political aspects that influenced each one of them. As an exploratory and descriptive research, uses the deductive method, as well as classic and contemporary literature review.